ANALYSIS OF THE BALANCE IN INDIVIDUALS WITH FREE BASE OF SUSTENTATION PRE-ESTABILESHED (Fiep Bulletin - online, 2015)
For the individual to have a good position the gravity center must be situated in the polygon of sustentation represented for the sole of the foot.  The feet examination in the erect position can be carried through by the electronic stabilometer that makes possible to analyze the continuous oscillations of the human body, aspects that are visually not noticed.  This study had as objective to carry through the comparative analysis registering the oscillations anteroposterior of the body of individuals with free base of sustentation and pre-established base of sustentation.  The study concluded that the imposed position of the feet can induce tactics of different corporal adjustment of the individual with free sustentation base, increasing the anteroposterior oscillations.  Being thus, the presented data demonstrate that the sole of the foot intervenes with the balance position and that the examination needs to be standardized; therefore the individual will always have the same positioning and behavior, making the results trustworthy.
Keywords: Feet; balance; posture.